ФИТОТЕРАПИЯ ЖАНА БИЙИК ТООЛОРГО АДАПТАЦИЯ (АДАБИЯТТАРГА ОБЗОР) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Food not only replenishes trophic and energy losses of the body, but is an information substrate that contributes to adaptation. Adaptogens and other food and medicinal plants are useful for adapting the body to the conditions of the highlands, correcting pre-posological and premorbid changes. Phytotherapy has a large arsenal of agents that contribute to successful adaptation to the conditions of the highlands. Studies of the influence of the alimental factor, the administration of medicinal plants in the process of adaptation, including to the conditions of the highlands, are promising.
Keywords: adaptation to highlands, adaptation and alimental factor, herbal medicine, adaptogens